Effect of Oral Honey Consumption on Immune Function Following Ex-Vivo Lipopolysaccharide Stimulation in Healthy Humans - McCarthy Olivia; Moser Othmar; L Eckstein Max; Deere Rachel; C Bain Steve; Dunseath Gareth; Bodger Owen; M Bracken Richard (International Journal of Nutrition, 2019)
Nine healthy individuals with a mean ± SD BMI of 22.0 ± 0.7 kg/m² and age of 20 ± 0.2 years, participated in this single-blind randomised, crossover trial investigating the impact of ingesting two different honeys (1) Tropical Forest Honey (TFH) and (2) Manuka Honey; strength 12+ (MAN) on circulating levels of plasma interferon gamma following ex-vivo lipopolysaccharide (LPS) stimulation. Blood samples were prepared into duplicate aliquots of whole blood (800 μl) and 100 μg/l of LPS was added to samples to give a final volume of 1 ml. Levels of IFN-γ in plasma fractions were measured via commercially available sandwich ELISA and all comparisons were made with paired data using the Wilcoxon Signed Rank test taking a significance level of 5%. Whilst significant intra-and-interpersonal variation was observed, IFN-γ concentrations remained statistically unchanged 48 hours after the ingestion of either honey (p=0.15). Thus, in this instance the type of honey did not influence the IFN-γ response to plasma samples spiked with LPS.
Keywords: Honey